Persistent developmental stuttering as a cortical-subcortical dysfunction: evidence from muscle activation Gagueira persistente do desenvolvimento como disfunção córtico-subcortical: evidências pela ativação muscular - Claudia Regina Furquim de Andrade; Fernanda Chiarion Sassi; Fabiola Juste; Lucia Iracema Zanotto de Mendonça (Arquivos de Neuro-Psiquiatria)
BACKGROUND: One contemporary view of stuttering posits that speech disfluencies arise from anomalous speech motor control. PURPOSE: To verify the rest muscle tension and speech reaction time of fluent and stuttering adults. METHOD: 22 adults, divided in two groups: G1 - 11 fluent individuals; G2 - 11 stutterers. Electromyography recordings (inferior orbicularis oris) were collected in two different situations: during rest and in a reaction time activity. RESULTS: The groups were significantly different considering rest muscle tension (G2 higher recordings) and did not differ when considering speech reaction time and muscle activity during speech. There was a strong positive correlation between speech reaction time and speech muscle activity for G2 - the longer the speech reaction time, the higher the muscle activity during speech. CONCLUSION: In addition to perceptible episodes of speech disfluency, stutterers exhibit anomalies in speech motor output during fluent speech. Correlations with a possible cortical-subcortical disorder are discussed. INTRODUÇÃO: Atualmente considera-se que as disfluências da fala na gagueira sejam decorrentes de controle motor anormal. OBJETIVO: Verificar o repouso e tempo de reação para fala em adultos fluentes e gagos. MÉTODO: 22 adultos, divididos em dois grupos: G1 - 11 fluentes; G2 - 11 gagos. Os dados eletromiográficos (orbicular dos lábios inferior) foram obtidos em duas situações: repouso e atividade de tempo de reação. RESULTADOS: Os grupos apresentaram diferenças significantes para a tensão muscular de repouso (G2 valores maiores) e não se diferenciaram quanto ao tempo de reação e atividade muscular de fala. Houve correlação positiva entre o tempo de reação e a atividade muscular de fala para G2 - quanto maior o tempo de reação maior a atividade muscular de fala. CONCLUSÃO: Além dos episódios perceptíveis de disfluência, gagos apresentam alterações no output motor de fala durante a produção da fala fluente. Correlações com possível distúrbio cortico-subcortical são discutidas.